The Influence of Work Environment on Employee Job Satisfaction at Turi Beach Resort Batam - Muhammad Arya Farraz Editra; Kurnia Illahi Manvi (Journal of Multidimensional Management, 2025)
The hospitality industry is a central pillar of global tourism growth, where service excellence and employee performance determine customer satisfaction and loyalty. In Indonesia, Batam has emerged as a strategic tourism hub due to its proximity to Singapore and Malaysia, driving rapid expansion of resort-based accommodations such as Turi Beach Resort Batam. Within this context, employee performance is strongly influenced by the work environment, encompassing both physical and non-physical factors that shape satisfaction, motivation, and productivity. This study investigates the effect of the work environment on job satisfaction among 150 employees selected from a population of 239 using Slovin’s formula with a 5% margin of error. Data were collected through a structured Likert-scale questionnaire, and instrument validity and reliability were confirmed through Pearson’s correlation and Cronbach’s alpha tests, with coefficients exceeding the 0.70 threshold. Classical assumption tests indicated that the data met normality, homogeneity, and linearity criteria. Regression analysis results showed a significant positive effect of the work environment on job satisfaction (F = 3.666; p = 0.031 < 0.05), with a determination coefficient (R²) of 0.063, meaning that 6.3% of job satisfaction variance was explained by the work environment, while the remaining 93.7% was influenced by other factors. The findings highlight that safe and supportive workplaces, combined with effective supervision and strong coworker relationships, are critical in fostering employee satisfaction. From a managerial perspective, this study underscores the importance of balancing physical conditions with broader human resource strategies, including compensation, promotion opportunities, and organizational culture, to sustain employee motivation and service quality in hospitality operations.